The Effect of Dividend Policy, Profitability, and Reporting Timeliness on Share Price Fluctuations of Listed Primary Consumer Goods Sector Companies on The Idx 2019-2023 Period - Muhammad Frezha Revito Arnanda; Dwi Urip Wardoyo (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of dividend policy, profitability, and timeliness of reporting on stock price fluctuations in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. This study uses a panel data regression method with the Random Effect Model (REM) approach processed through EViews software. The sample consists of 15 companies with a total of 75 observations (balanced panel). The F-test results show that simultaneously the three independent variables have a significant effect on stock price fluctuations (F-statistic = 15.713; Prob = 0.000). Meanwhile, the t-test results show that only the ROA variable has a positive and significant partial effect on stock prices (t = 6.645; Prob = 0.000), while the DPR variables (t = -1.483; Prob = 0.142) and timeliness of reporting (t = 0.698; Prob = 0.487) have no significant effect. The R-squared value of 0.399 indicates that the model can explain 39.9% of the variation in stock price fluctuations, while the rest is influenced by other factors outside the model. This finding emphasizes the importance of profitability as a key indicator in influencing stock price movements, compared to dividend policy and timeliness of reporting. This study provides practical implications for company management and investors in financial performance-based decision making.